슬관절 주위 골절이 동반된 슬관절 치환술의 Klebsiella pneumoniae 단일균에 의한 후기 감염 - 정철용(Chul-Young Jung); 은일수(Il-Soo Eun); 고영철(Young-Chul Ko); 박만준(Man-Jun Park); 김민우(Min-Woo Kim); 황금민(Keum-Min Hwang) (The journal of the Korean Orthopaedic Association, 2013)
Klebsiella pneumoniae에 의해 발생한 화농성 관절염은 성인에서 매우 드물며, 인공관절 치환술 후 발생한 경우는 더욱 드물다. 인공관절 치환술 후 발생한 K. pneumoniae에 의한 화농성 관절염은 급성 또는 수술 후 초기에 발생한 예는 있으나 후기 감염으로 보고된예는 국내에서 아직 보고된 바 없으며, 다균성 감염이 대부분으로 K. pneumoniae 단일균에 의한 감염 역시 매우 드물다. 이에 저자들은 내원 11년 전 슬관절 인공관절 치환술을 받은 85세 여자 환자에서 후기 감염으로 K. pneumoniae 단일균에 의한 화농성 관절염이 슬관절 치환물 주위 골절과 동반된 1예를 치험하였기에 보고하고자 한다. Septic arthritis caused by Klebsiella pneumonia in adults is rare and is rarely observed after total knee arthroplasty. Acute or early onset of septic arthritis caused by K. pneumoniae has been reported after total knee arthroplasty. However, to date the only one overseas case of late K. pneumoniae infection after total knee arthroplasty has been reported, with no such case in Korea. In addition, monomicrobial infections by K. pneumoniae are not frequently found but are found primarily in the form of polymicrobial infections. The purpose of this paper is to report on a case in which an 85-year-old female patient, who had undergone a total joint arthroplasty 11 years ago, developed the late onset of septic arthritis caused by monomicrobial K. pneumonia infection with a periprosthetic fracture through literature reviews. KCI Citation Count: 0